Assessment Of General Ocular Health And Visual Status Of The Small-Scale Industrial Workers (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: Incidence of visual disorders in industrial workers may result in visual loss, anguish, reduced  manpower, man hours and economic loss. Most of these hazards are preventable if adequate  precautionary measures are taken. [8,11] Worker’s eyes may be exposed to a variety of dangerous  agents depending on the type of industry which may constitute an occupational hazard.  According to OSHA, personal protective equipment is devices design to protect workers’ eyes  from severe work place injury or illness resulting from contact with metal splash, chemical  splash, dust, flying particle or radiation. [14,16] So the aim of the study is to assess Ocular Health,  Visual & Refractive status of the workers working in the metal machinery (small scale)  industries. METHODS: A clinical examination of the workers was accompanied by detailed occupational history in the  small scale & tiny sector metal machinery industries. Visual acuity was measured using  Snellen’s chart for distance and N notation reading chart for near. Color vision testing was  done with Pseudoisochromatic-Ishihara chart. Anterior segment of eye was examining with the  help of torch light and SLE. Fundus evaluation was done with the help of direct  ophthalmoscope. Objective & Subjective Refraction was performed using Retinoscope and  trial case. Stereopsis was measured with the help of Titmus Fly test. RESULTS: Hundred and eighty small scale industry workers were screened. Among them, all were male  with a mean age (45.5 ± 11.31 years). 74% showed Visual impairment. The most common  visual disorders were uncorrected presbyopia 65% (117), uncorrected refractive error 59%  (106) out of which 17% (30) were already use their own spectacle prescription remaining 42%  (76) were prescribed new spectacle. Color vision defect was found in 2% (3). Out of hundred  and eighty only 11% (19) of the workers were use protective eye wear, remaining 89% (161)  of them were never use protective eye wears on daily basis. CONCLUSION:This study concluded that uncorrected refractive error and uncorrected presbyopia was high  among workers as they are not aware about eye health and safety measures for the occupation.  The use of safety eye devices is low among workers and recommends that process about  awareness and implementation of ocular safety in these industries is established as occupational  protective measures are important for metal machinery industrial workers who are at a high  risk of eye injuries. It is recommended that, there is a need to review the design, and reinforce  the strict implementation of occupational eye safety programs.
Keywords: Visual acuity; Refractive error; Presbyopia; Industrial workers; Fundus; Stereopsis; Color vision; Personal Protective Equipment